Memory consolidation in honey bees is enhanced by down-regulation of Down syndrome cell adhesion molecule and changes its alternative splicing - Ustaoglu, Pinar; McQuarrie, David W. J.; Rochet, Anthony; Dix, Thomas C.; Haussmann, Irmgard U.; Arnold, Roland; Devaud, Jean-Marc; Soller, Matthias (Frontiers in Molecular Neuroscience, 2024)
Down syndrome cell adhesion molecule (Dscam) gene encodes a cell adhesion molecule required for neuronal wiring. A remarkable feature of arthropod Dscam is massive alternative splicing generating thousands of different isoforms from three variable clusters of alternative exons. Dscam expression and diversity arising from alternative splicing have been studied during development, but whether they exert functions in adult brains has not been determined. Here, using honey bees, we find that Dscam expression is critically linked to memory retention as reducing expression by RNAi enhances memory after reward learning in adult worker honey bees. Moreover, alternative splicing of Dscam is altered in all three variable clusters after learning. Since identical Dscam isoforms engage in homophilic interactions, these results suggest a mechanism to alter inclusion of variable exons during memory consolidation to modify neuronal connections for memory retention.